More or less ambition in the Doha Round? The development impact of recent proposal - Bouët, Antoine; Mevel, SImon; Orden, David (Wiley, 2006)
We analyse the impact on developing countries, whose economies depend heavily on agriculture, of a WTO Doha Development Round agreement based on greater or lesser levels of ambition. We present the results of an ambitious versus an unambitious Doha Round outcome, using the MIRAGE model of the global economy, with a special focus on developing countries. Our simulations are based on negotiating proposals from the run‐up to the Hong Kong ministerial meeting but not agreed upon in December 2005. We compare those outcomes with the estimated effects of full global trade liberalization. The results for the two Doha scenarios demonstrate the high stakes of this negotiation given the positions of EU, US and the G‐20 coalition. A successful round could deliver real gains both globally and for developing countries, but the magnitude of those gains depends on the shape of the agreement. A reform outcome based on the most ambitious components of the negotiating proposals of the US and EU delivers noticeably greater benefits than an unambitious outcome. Developing countries are exposed to very contrasting fortunes. The details matter in the differing proposals, such as the tariff and domestic support reduction formulae, tariff caps, and number of sensitive and special products. Negotiating commitment and diligence are needed in 2006 to avoid a hollow Doha outcome given the technical character of these details.